DIVERSITY SPECIES OF EBONI (Diospyros spp.) TULABOLO-PINOGU RESORT, BOGANINANI WARTABONE NATIONAL PARK, NORTH SULAWESI - Ady Suryawan; Julianus Kinho (Widyariset, 2012)
Biological diversity was an invaluable asset because it had amazing potency. The uniqueness of nature and its climate had put Indonesia as megabiodiversity country. In other side, high exploration of resources and policies have a little concern on ecology and biodiversity preservation had threatened sustainability of species. Regulation of Forestry Minister number 324/2010 stated Tulobolo-Pinogu Resort of Boganinani Wartabone National Park as a limited production forest. According Government Regulation Number 7/1999, ebony (Diospyros spp.) was protected species. The objective of this research was to inventory all of tree species in Tulabolo-Pinogu especially eboni as to attempt of biodiversity conservation. This study used transect lines method with 3 hectare sampling area. This research found 6 species of ebony, 3 has been reported that D. buxifolia, D. minahassae and D. korthalsiana, 3 newly reporte D. cauliflora, D. malabarica and D. pilosanthera. All of ebony were found is very limited and vulnerable.